Kadar Transthyretin Plasma pada Lanjut Usia Sarkopenia dan Non-Sarkopenia - Fahrurozi, R. Ifan A.; Martini, Rose D; Mulyana, Roza; Murni, Arina W; Decroli, Eva; Miro, Saptino; Viotra, Deka; Yoga, Vesri (UI Scholars Hub, 2025)
Introduction. Sarcopenia is a geriatric syndrome marked by an age-related decline in muscle mass, which is affected by protein intake. Transthyretin is a visceral protein used to evaluate nutritional status and acts as a positive regulator of muscle mass. This study aimed to assess the difference in plasma transthyretin levels between elderly groups with and without sarcopenia. Methods. This was an analytical observational study with a cross-sectional approach. Subjects were elderly patients who visited the Internal Medicine Polyclinic of Dr. M. Djamil Hospital Padang and met the inclusion and exclusion criteria from August to September 2024. Subjects were classified into sarcopenic and non-sarcopenic groups, followed by an examination of plasma transthyretin levels. Sarcopenia was diagnosed using bio-impedance analysis (BIA) measurement, handgrip strength with a Jamar hydraulic hand dynamometer, and physical performance with a walking speed test. Plasma transthyretin levels were measured using the enzyme-linked immunosorbent assay (ELISA) method. Comparative analysis was performed using the unpaired T-test using SPSS 29.0. Results. Among total of 46 subjects who participated in this study, the majority of elderly individuals with sarcopenia were predominantly female. The mean plasma transthyretin level in the sarcopenic elderly group was 10.9 (3.3) mg/dL, while in the non-sarcopenic elderly group was 20.3 (2.5) mg/dL. Comparative analysis demonstrated a significant difference in plasma transthyretin levels between sarcopenic and non-sarcopenic elderly individuals (p < 0.001). Plasma transthyretin levels in the sarcopenic elderly group were lower compared to the non-sarcopenic elderly group. Conclusion. There is a significant difference in plasma transthyretin levels between sarcopenic and non-sarcopenic elderly individuals.